Upaya Pasangan Suami Istri Dalam Menjaga Keharmonisan Keluarga Di Desa Rowotengah - Rachmawati, Jannah Wulida Indana; Izah, Desi Firial Nuril; Hidayah, Lailul; Fitriana, Ani Qotuz Zuhro’ (CV. ITTC INDONESIA, 2023)
This study was motivated by wanting to know how the efforts of married couples in maintaining family harmony located in rowotengah village. The subjects of this study were 2 married couples who have been married for 5 years and above. This research method uses a qualitative approach that aims to explain a phenomenon of family harmony. The results of this study prove that married couples in Rowotengah village in maintaining family harmony are accepting each other, being responsible, quality time (spending time with family), always giving news, giving each other support, deep talk (serious talk), not telling problems to others (parents/in-laws). The characteristics of family harmony in Rowotwngah Village are such as Creating a religious life, Mutual respect between fellow families, The quality and quantity of conflicts are minimal, There is a close relationship or bond.